Bovine teeth can reliably substitute human dentine in an intra‐tooth push‐out bond strength model?. (20th February 2019) - Silva, E. J. N. L.; Carvalho, N. K.; Prado, M. C.; Senna, P. M.; Souza, E. M.; De‐Deus, G.
Abstract: Aim: To investigate the reliability of using bovine teeth as an alternative to human teeth in an intra‐tooth push‐out model by comparing the bond strength of three root canal sealers in both tooth substrates. Methodology: From human and bovine incisors (12 per group), one 1‐mm disc was obtained from each root. On each disc, three standard 0.8‐mm‐diameter holes were drilled through the dentine. After irrigation, the holes were filled with one of three root canal sealers: AH Plus, MTA Fillapex or Total Fill BC Sealer. Tooth slices were kept in contact with sterile gauze moistened in PBS solution (pH = 7.2) for 7 days at 37 °C, and finally, a push‐out load was applied until sealer dislocation. The bonded interface area was calculated to obtain data in MPa. The push‐out data for each sealer and the overall push‐out data for human and bovine teeth were compared (Mann–Whitney U ). Kruskal–Wallis was used to study the sealers behaviour at each of the dental substrates. Multiple comparisons were performed using Mann–Whitney U after Bonferroni correction ( P < 0.05). Results: Dentine substrate did not influence the push‐out of either individual sealers or overall sealers tested (Mann–Whitney U, P > 0.05). In both human and bovine samples, AH Plus performed better than BC Sealer and MTA Fillapex, whilst BC Sealer also provided a superior push‐out compared to MTA Fillapex (Mann–Whitney U, P < 0.05). Conclusion: When using an intra‐tooth model, bovine teeth did not significantly influence the bond strength of sealers.